2016
DOI: 10.2147/ndt.s103432
|View full text |Cite
|
Sign up to set email alerts
|

Does early improvement in depressive symptoms predict subsequent remission in patients with depression who are treated with duloxetine?

Abstract: PurposeIn this prospective study, we examined whether early reduction in depressive symptoms predicts later remission to duloxetine in the treatment of depression, as monitored using the Montgomery–Asberg Depression Rating Scale (MADRS).Patients and methodsAmong the 106 patients who were enrolled in this study, 67 were included in the statistical analysis. A clinical evaluation using the MADRS was performed at weeks 0, 4, 8, 12, and 16 after commencing treatment. For each time point, the MADRS total score was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Approximately 40%–70% of the patients who are suffering from depression react positively to the treatment with the antidepressant for at least 2 months. 1 – 5 Approximately 80% of them respond to the first or second choice of a recommended antidepressant. Despite the relatively high antidepressant efficacy, the level of treatment resistance is relatively high.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 40%–70% of the patients who are suffering from depression react positively to the treatment with the antidepressant for at least 2 months. 1 – 5 Approximately 80% of them respond to the first or second choice of a recommended antidepressant. Despite the relatively high antidepressant efficacy, the level of treatment resistance is relatively high.…”
Section: Introductionmentioning
confidence: 99%
“…A re-analysis of the STAR*D trial reported that an early improvement in core depressive symptoms within two weeks predicted a higher probability of eventual remission [14]. Another study involving 67 patients treated with duloxetine found that early improvement in specific individual symptoms, including dysphoria and retardation, after four weeks of intervention significantly correlated with subsequent remission [33]. Assessing individual symptoms in conjunction with the overall depression assessment score could enhance our ability to predict treatment outcomes and allow for more personalized therapeutic strategies [34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“… 6 , 7) To overcome this challenge in the treatment of depression, there have been many clinical trials to investigate better treatment strategies for treatment-resistant individuals. In addition, there have been many studies investigating predictors of treatment outcomes, such as early treatment improvement, 8) characteristics of the depressive episode, 9) patient characteristics, 10 , 11) and more. Clinicians should consider accumulated research findings when choosing a relevant treatment strategy in various clinical practice scenarios, which increases the need for the development of treatment guidelines.…”
Section: Introductionmentioning
confidence: 99%